2020
DOI: 10.2147/ndt.s263537
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cognitive Behavioral Therapy Reduces Benzodiazepine Anxiolytics Use in Japanese Patients with Mood and Anxiety Disorders: A Retrospective Observational Study</p>

Abstract: Purpose Benzodiazepines (BZDs) are prescribed to treat psychiatric diseases. However, many guidelines recommend limiting the use of BZDs because of side effects and lack of evidence regarding long-term efficacy. Moreover, reducing BZDs’ use is difficult because of dependency and the severity of withdrawal symptoms. The efficacy of cognitive behavioral therapy (CBT) for mood and anxiety disorders has been demonstrated. However, there is scant evidence that CBT has effectively reduced BZDs use, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The association between symptom deterioration and increase in drug dosage was higher in F 4 than in other diagnostic categories. It might be partially reflected in the high risk of benzodiazepine dependence in the pharmacological treatment of anxiety (O’Brien, 2005), and in the limitation of cognitive behavioral therapy in Japan, which may be a challenge for the future (Nakajima et al, 2020). New physical symptoms were seen in F 2.…”
Section: Discussionmentioning
confidence: 99%
“…The association between symptom deterioration and increase in drug dosage was higher in F 4 than in other diagnostic categories. It might be partially reflected in the high risk of benzodiazepine dependence in the pharmacological treatment of anxiety (O’Brien, 2005), and in the limitation of cognitive behavioral therapy in Japan, which may be a challenge for the future (Nakajima et al, 2020). New physical symptoms were seen in F 2.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is considered that these guidelines are effective in changing the prescription trend, and publishing a method for reducing dosages and number of drugs for BZRAs in these guidelines would help in changing prescription trends. As methods for reducing prescription amount of BZRAs, psychological therapy or education, such as cognitive behavioral therapy are used [ 25 , 26 , 27 ], and a method of reducing BZRAs prescriptions in clinical practice is required. Otherwise, it will be effective to launch medical fee revisions concerning the prescribed number of BZRAs to reduce the number of BZRAs.…”
Section: Discussionmentioning
confidence: 99%
“…There can be several reasons for BZ monotherapy without SSRIs in the treatment of patients with anxiety disorders. First, the prescription rate of BZ anxiolytics is higher in Japan than in other countries 5 . Such regional characteristics may contribute to BZ monotherapy without SSRIs.…”
Section: Introductionmentioning
confidence: 99%
“…First, the prescription rate of BZ anxiolytics is higher in Japan than in other countries. 5 Such regional characteristics may contribute to BZ monotherapy without SSRIs. Second, previous studies have reported that there was sex difference in the prescription of BZ anxiolytics.…”
Section: Introductionmentioning
confidence: 99%